REVOLUTIONIZING EDUCATION: HARNESSING THE POWER OF ARTIFICIAL INTELLIGENCE FOR PERSONALIZED LEARNING - Muh. Putra Pratama; Rigel Sampelolo; Hans Lura (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2023)
Rapid advances in artificial intelligence (AI) have opened up new possibilities in various fields, and education is no exception. Traditional one-size-fits-all teaching methods are gradually being replaced by personalized learning experiences made possible through AI technology. This article explores how AI is revolutionizing education by tailoring the learning experience to individual students' needs, increasing engagement, and improving overall learning outcomes. The research method used in this study is a qualitative descriptive method by utilizing questionnaires, interviews, observations and documentation in data collection. The results of the questionnaire related to the Importance of AI in Learning, obtained data that 88% of students strongly agree, 9% agree, 2% disagree, and 1% strongly disagree about the importance of AI in helping learning. The results of the questionnaire related to AI as an Alternative to Self-Learning, obtained data that 74% of students strongly agree, 7% agree, 14% disagree, and 5% strongly disagree about AI as an alternative to independent learning. The results of the questionnaire related to AI becoming Virtual Tutors and Smart Assistants, obtained data that 88% of students strongly agree, 9% agree, 2% disagree, and 1% strongly disagree about AI as being able to be used as a virtual teacher or intelligent assistant. The results of the questionnaire related to AI can replace teachers / lecturers, data were obtained that 11% of students strongly agreed, 9% agreed, 23% disagreed, and 57% strongly disagreed regarding AI can replace teachers / lecturers.